Pharmacists and maternal-fetal medicine: development of a tool to characterize knowledge and current clinical practice. (April 2014) - Bains, Serena; Rowe, Hilary; Wilby, Kyle J
Abstract Objective: To develop a knowledge assessment tool to assess baseline knowledge and current practice regarding maternal-fetal medicine. Methods: A literature search was complemented with categorization of questions under five predefined domains related to maternal-fetal medicine. The final questionnaire was sent for expert review, cultural adaptation, and piloting, with feedback incorporated accordingly. Results: A questionnaire was developed consisting of questions pertaining to demographics, knowledge, and current practice. Conclusions: This tool is of interest to researchers, educators, and clinicians aiming to assess baseline knowledge, current curricula (both entry-to-practice and graduate) and continuing education opportunities for practicing pharmacists.